The integral, a vision of its evolution through time III - Ortiz Fernández, Alejandro (2023)
In this opportunity we present some areas of the evolution of the integral, which complement what was deal with in parts I and II. Thus we give a conceptual overview of the McShane integral, of the C-integral, of the Bochner integral, of the Lm HK integral , of the integral on manifolds and on a modern point of view of the Riemann integral.